Unspoken Influence: Presupposition, Implicature, and Hypnotic Ambiguity in Indonesian Political Interviews - Priadi, Arum (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This study analyzes forms of covert linguistic influence in Indonesian political interviews, focusing on three primary strategies: presupposition, conversational implicature, and hypnotic ambiguity. Political communication functions through explicit message content and implicit utterances subtly and systematically shaping public opinion. The research aims to uncover how suggestive politicians and interviewers employ strategies to frame meaning without making direct claims. The study adopts a qualitative discourse analysis approach grounded in cognitive pragmatics. Data were drawn from ten political interview transcripts broadcast on national television and digital platforms between 2019 and 2024. Analysis was conducted using the framework of Relevance Theory (Sperber & Wilson) and hypnotic language models (Erickson & NLP). Analytical tools such as AntConc were used to map the distribution of keywords and contextual usage of suggestive phrases. Findings indicate that presupposition emerged as the most dominant strategy (28.5%), followed by implicature (23.8%) and semantic ambiguity (15.7%). Additionally, hypno questioning (14.2%), embedded commands (10%), and vocal emphasis (7.6%) were identified as supplementary techniques that enhance suggestion at both affective and inferential levels. The study also reveals that strategy usage varies depending on the media platform, interview style, and the politician's background. Conceptually, this research extends the application of pragmatic theory to local political contexts and demonstrates that language is a latent tool of influence operating at both cognitive and emotional levels. The study contributes to political linguistics and offers a new analytical framework for examining implicit communication in public discourse. Practical implications include strengthening media literacy, promoting ethical political communication, and enhancing critical education regarding suggestive influence in digital democracy.